Anti fuzzy bi-ideals on ordered AG-groupoids - Nasreen Kausar; Mohammad Munir; Muhammad Gulzar; Gezahagne Mulat Addis; Rukhshanda Anjum (IndoMS, 2020)
The purpose of this study is to initiate the notion of anti fuzzy left (resp. right, bi-, generalized bi-, (1,2)-) ideals in non-associative and non-commutative ordered semigroups. We characterize different classes of non-associative and non-commutative ordered semigroups in terms of such ideals.